Clinicians' knowledge, attitudes and behaviours towards evidence-based practice using clinical presentations of dizziness and vertigo as an exemplar - Clarke, Richard Matthew (Department of Health and Rehabilitation Sciences, 2023)
Evidence-based practice (EBP) is an approach to clinical decision-making that incorporates well-researched and established scientific knowledge with other sources of knowledge such as practitioner experience, patient preferences, and clinical context. Use of EBP aims to provide standardised care, which is rooted in the best available evidence. Among the most important and arguably clinically relevant outcomes of EBP are Clinical Practice Guidelines (CPG), which cover a variety of topics in medicine and associated professions. CPG exist for vestibular conditions, which are prevalent in the general and medical populations. Nevertheless, there is some suggestion that EBP regarding dizziness is sub-optimal in wealthy countries, and little is known about CPG use in LMIC, particularly across the professions that would be expected to use them. However, despite the availability and proliferation of evidence in the health sciences, research has shown that uptake and utilisation of EBP is poor even in the Global North. In low- and middle-income countries (LMIC) such as South Africa where resources are scarce, previous research has suggested that additional challenges exist which are specific to the developing context. There is, however, little research on translation of EBP into clinical practice. Thus, this study sought to investigate the knowledge, attitudes, and practices towards evidence-based practice of a specific subset of South African clinicians (audiologists, otorhinolaryngologists, and physiotherapists) in South Africa, using assessment and management of dizzy patients as an exemplar. Mixed methodology achieved the study's aims. Phase one employed a two-part questionnaire. Fifty-four participants, comprising 37 audiologists, five Ear, nose and throat surgeons (ENTs), and nine physiotherapists were surveyed to identify their orientation towards EBP using the Evidence-Based Practice Profile Questionnaire (EBP2Q). Independent samples t-tests and one-way ANOVAs were used to analyse the EBP2Q data. Three cases of common vestibular pathologies (Ménière's disease, vestibular migraine, and persistent postural perceptual dizziness) based on the CPG, were developed by the researcher and a Delphi panel of experts. Survey participants answered questions regarding implementation of CPGs in each case. Cases were scored according to matches with the CPGs. Phase two adopted a qualitative, descriptive approach and comprised four mini focus groups with a total of 10 participants representing the three professions surveyed. The focus groups aimed to explore participants' self-perceived barriers and facilitators to the use of EBP in general as well as in the context of dizzy patients. The most clinically relevant result was that the case questionnaire analysis revealed that approximately half of participants were able to identify Meniere's disease and vestibular migraine, whereas only one quarter of participants could identify the case of functional dizziness. Focus groups revealed barriers to the use of EBP such as lack of access to research and lack of time to research. Furthermore, participants recognised that the complexity of dizzy patients had led to sub-optimal assessment and management of such patients. Quantitative results of the current study suggested that participants with additional exposure to research through postgraduate training had higher scores on the EBP2Q in four out of five domains and the total questionnaire score than those with undergraduate training only. These results were consistent with previous research from wealthy countries which suggested that increased exposure through postgraduate training and working at academic facilities results in better orientation towards EBP. However, mean domain scores amongst participants in studies from wealthy countries appear to be higher than those from the sample on the current South African study, although it is difficult to tell whether the difference is statistically significant. Additionally, there was no apparent influence of years' experience on orientation towards EBP, contradicting what has been found in previous research. Outcomes of the study suggest that while healthcare practitioners have good attitudes towards EBP, it is more effectively implemented by clinicians with postgraduate training. Further, ease of access and exposure to research is the greatest facilitator to use of research and EBP by clinicians. Despite that, barriers to uptake and utilisation of EBP such as lack of access to research, lack of contextually relevant research, and low confidence at appraising literature were described. In addition, barriers common to the Global North and Global South were recognised such as lack of time to conduct literature searches and overburdening of clinical staff. Finally, a gap was noted in the knowledge of practitioners managing dizzy patients, specifically regarding patients with functional dizziness. Thus, this study highlights the need for use and application of EBP to the management of dizzy patients. Additional training of audiologists, ENTs and physiotherapists may be required regarding effective, multidisciplinary management of dizzy patients.